The Influence of Organizational Culture, Work Environment, and Leadership Style on Work Motivation and its Impact on Job Satisfaction of Generation Z Civil Apparatus (ASN) in the Bandung Regency Government - Reni Rahmawati; Gurawan Dayona Ismail; Nunung Ayu Sofianti; Yoyo Sudaryo; Andre Suryaningprang (Eduvest - Journal of Universal Studies, 2026)
The research background is based on the conditions of Generation Z entering the workforce and their distinct work expectations. This study aims to analyze the influence of Organizational Culture, Work Environment, and Leadership Style on Work Motivation and their impact on the Job Satisfaction of Generation Z Aparatur Sipil Negara (ASN) in the Bandung Regency Government. The research method employs a descriptive and verification approach, utilizing questionnaires for data collection and Structural Equation Modeling (SEM) for analysis. The findings indicate that Organizational Culture, Work Environment, and Leadership Style have a positive and significant effect on Work Motivation. Directly, Organizational Culture and Leadership Style significantly influence Job Satisfaction, whereas Work Environment does not have a significant effect. Work Motivation is shown to have the most dominant influence on Job Satisfaction and acts as a mediator in the relationship between Organizational Culture and Job Satisfaction, but does not mediate the influence of Work Environment and Leadership Style on Job Satisfaction. Overall, the study highlights the importance of strengthening organizational culture, promoting adaptive leadership, and enhancing motivational aspects to support the job satisfaction of Generation Z civil servants in facing bureaucratic transformation.